To Study the Physicochemical Basis of the Processes of Dyeing and Printing of Mixed Fiber Materials - Shukrullayev Shamsiddin Najmiddin ogli; Razzokov Hasan Qalandarovich; Ortiqov. Sh.Sh (Genius Journals, 2022)
The article focuses on the preparation and physicochemical properties of dyes for dyeing composite fibers, provides a number of comments and examples, and describes its role in a number of studies. In addition, the physicochemical properties of mixed fibers were studied.
Keywords: Mixed fiber; research; shlichta; mane